P022 An investigation into the effects of a 20-minute nap-opportunity on cognitive function in students aged 18–30. (19th November 2019) - Haddad, Suraiya; Rahman, Rezwana; Wong, Felyx; Jackson, W; Morrell, Mary
Abstract : Introduction: Sleep-deprivation is increasing in prevalence and compensatory napping is becoming common practice. Little is known about the cognitive benefits derived from a nap in sleep-deprived individuals, or within the student population. Furthermore, few studies have investigated the cognitive benefits of napping using the incongruent Stroop test. This study aimed to investigate the effects of a nap-opportunity on cognitive function in individuals aged 18–30. Methods: A randomised, crossover study was conducted. Participants were recruited from Imperial College London and were allocated to either control (no nap-opportunity) or intervention (20-minute nap-opportunity) groups. The incongruent Stroop test was used to measure reaction time (RT) and percentage accuracy, which were used as markers of cognitive function. ΔRT and Δ percentage accuracy, between control and nap-opportunity groups were compared. Paired and unpaired t-tests were used for the analysis of RT. Wilcoxon signed-rank and Mann-Whitney-U tests were used to test the percentage accuracy. The study was approved by the Imperial College Medical Education Ethics Committee. Results: Participants (n=29) had a mean age of 20 (SD±1.4) years, 55% male. In those who were acutely sleep-deprived, the RT improved in the intervention group following a 20-minute nap-opportunity, compared to the control group (p=0.01; figure 1 ). Overall, no significant difference in Δ percentage accuracy was observed between the control and nap-opportunity groups (p=0.31). Conclusions: The main finding of this study was that the sleep-deprived group derive greater benefit in cognitive function from a 20-minute nap-opportunity. Future studies could investigate the relationship between the amount of sleep-deprivation and the magnitude of benefit derived from a nap-opportunity. Moreover, the impact of napping in individuals who are chronically sleep-deprived should also be explored.